2018
DOI: 10.22207/jpam.12.4.67
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of Candida Species in Patients with Vulvovaginal Candidiasis

Abstract: Abnormal vaginal discharge is one of the frequent complaints of women of reproductive age group. This study was carried out to determine the prevalence of vulvovaginal candidiasis(VVC) among the patients attending the tertiary care hospital with complaints of suggestive of vaginitis. This study was done in a tertiary care hospital, Chennai for a period of 1 year from January 2017 to December 2017. The study included 160 women of the age group 15 -65 years with complaints suggestive of vaginitis. High vaginal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
2
6
1
Order By: Relevance
“…The prevalence of non-albicans species in this study was as follows Candida glabrata which was 12(9.4%), Candida parapsilosis 4(3.5%) and the lowest percentage belonged to Candida kruis 2(1.2%). The study observed results similar to two studies done by (Krishnasamyetal) and (salvietal) by which they found that the highest parentage of Candida spp isolated was Candida albicans and also regarding the NAC which was similar to our study: Candida glabrata (11%), Candida parapsilosis (11%) and Candida kruis (2%) (15) , (11) . A study done by (Jayalakshmi etal.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The prevalence of non-albicans species in this study was as follows Candida glabrata which was 12(9.4%), Candida parapsilosis 4(3.5%) and the lowest percentage belonged to Candida kruis 2(1.2%). The study observed results similar to two studies done by (Krishnasamyetal) and (salvietal) by which they found that the highest parentage of Candida spp isolated was Candida albicans and also regarding the NAC which was similar to our study: Candida glabrata (11%), Candida parapsilosis (11%) and Candida kruis (2%) (15) , (11) . A study done by (Jayalakshmi etal.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, out of 300 symptomatic patients, candidiasis was detected in (57%) (171/300) cases on the culture of the high vaginal swab, and this data is similar to reports by (Rad, etal) (12) which were (66%) and (Kalia, etal) (13) (47%), and lower than that reported by (Ugwa) (14) who reported (84.5%) in North-West Nigeria. Our result is higher than reported by (Krishnasamyetal) (15) , which had done on 160 women, and 56 high vaginal swabs were (35%) positive culture revealed candida spp. and higher than reported by (10) which was (30.6%).…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…Studying hormone-sensing pathways help in explaining gender bias-associated infections. C. albicans is recorded as the predominant colonizer in the female reproductive tract and a major cause of genital thrush ( 29 ). The shift in the frequency from albicans to NAC such as C. glabrata , C. parapsilosis , C. tropicalis may be due to increased use of the counter drugs, a short-course of antifungal therapy, and long-term use of azoles ( 30 ).…”
Section: Discussionmentioning
confidence: 99%